Rancangan Program Biblioterapy pada Remaja Berbasis Asesmen Kepercayaan Diri - Rahma Wira Nita; Randa Gunawan (Jurnal Counseling Care, 2020)
ABSTRACT This research is motivated by the indications of adolescents who have self-confidence barriers. This article aims to come up with a formula in the form of a counseling service program in the form of bibliotherapy services for students who have self-confidence barriers. The research method used in this research is descriptive quantitative. The population of this research is the teenagers of Class XI, amounting to 344 people, the sample in this study is 77 people who are taken, namely proportional random sampling technique. Data collection instrument using a questionnaire. The data were analyzed using the percentage technique. The results of the identification of adolescents' : 1) self-confidence in learning at Rao State High School 1, Pasaman Regency are on Medium criteria including: Having a sense of security, confidence in their own abilities, not being selfish, independent and optimistic.2)  idividually or in groups such as material on believing in one's own abilities and Optimistic in learning, developing self-efficacy and tips for increasing self-confidence. The design of the bibliotherapy service program is either in individual or group formats. With bibliotherapy media in the form of books, print and electronic, audio, video, in order to increase the confidence of students in learning. Key Word : self-confidence, Counseling Service, Biblioterapy ABSTRAKPenelitian ini dilatarbelakangi adanya indikasi remaja yang memililiki hambatan kepercayaan diri. Artikel ini bertujuan memunculkan formula berupa program pelayanan konseling dalam bnetuk layanan biblioterapy bagi peserta didik yang memiliki hambatan kepercayaan diri. Metode penelitian yang digunakan dalam peneliian ini yaitu deskriptif kuantitatif. Populasi penelitian adalah remaja Kelas XI yang berjumlah 344 Orang, sampel dalam penelitian ini 77 orang yang diambil yaitu  teknik proposional random sampling. Instrumen pengumpul data dengan menggunakan angket. Data dianalisis menggunakan teknik persentase. Berdasarkan hasil penelitian terungkap bahw: 1) kepercayaan diri remaja dalam belajar di SMA N 1 Rao berada pada kriteria Sedang meliputi: Memiliki rasa aman, yakin pada kemampuan diri sendiri, tidak mementingkan diri sendiri, mandiri dan Optimis. 2) Rancangan Program Pelayanan Konseling berupa layanan biblioterapy baik secara individu maupun kelompok seperti materi tentang  yakin pada kemampuan diri sendiri dan Optimis dalam belajar, mengembangkan kemampuan diri dan kiat meningkiatkan kepercayaan diri. Rancangan program layaan biblioterapy baik dalam format individual, kelompok. Dengan media biblioterapy berupa buku, cetak dan elektonik, audio, video, dalam rangka meningkatkan Kepercayaan diri peserta didik dalam belajar. Kata Kunci : Kepercayaan Diri, Layanan Konseling, Biblioterapy.